Tantangan dan Strategi Inovatif Guru SKI dalam Mengajar Kitab Khulāṣah Nūr al-Yaqīn di Madrasah Tsanawiyah - Ibnu Hafid Alfarisy (Tasqif: Journal of Islamic Pedagogy, 2026)
This research aimed to explore the challenges inherent in teaching Islamic Cultural History (SKI) through the classical Arabic text Khulāṣah Nūr al-Yaqīn, while also examining novel strategies grounded in Pedagogical Content Knowledge (PCK) utilized by SKI instructors at MTs Al Irsyad Tengaran 7, Batu City. Employing a qualitative case study methodology, data were gathered via comprehensive interviews with SKI teachers possessing master’s degrees, alongside an analysis of instructional materials, and subsequently analyzed through thematic analysis. The results of this study identified six primary challenges: students’ historical misunderstandings, the restricted scope of textual coverage, the prevalence of lecture–translation approaches, the limited efficacy of instructional media, the substantial workload teachers face in supplementing references, and the complexities of classroom management. To surmount these obstacles, the teacher formulated four interconnected PCK -based strategies: contextual storytelling incorporating multi-classical references, the utilization of authentic visual media, interactive apperception via real-life analogies, and the elevation of teacher professionalism. Theoretically, this study strengthened the conceptualization of domain-specific PCK in teaching classical Arabic texts within the context of Islamic secondary education. Practically, the results underscored the necessity for focused teacher training, curriculum design, and additional research concerning classical text-based learning across varied madrasah settings.